Modernisasi Pesantren dalam Konstruksi Nurcholish Madjid - Mukaffan Mukaffan; Ali Hasan Siswanto (IAIN Ponorogo, 2019)
Abstract: One of Nurcholish Madjid's thoughts contributions in Indonesia is revealing the importance of modernizing education in pesantren. Thus, some problems will be discussed in this research. First, how is the ideal goal of Pesantren according to Nurcholish Madjid? Second, how is Nurcholish Madjid's view of the ideal pesantren curriculum in the modernization era? To answer these problems, researchers employed a qualitative research method with a content analysis approach using library research. Based on the reading model, Nurcholish Madjid advocated several views. First, the formulation of pesantren’s objectives must keep abreast of the times. Second, pesantren must be a solution to the needs of students in this modern era. In these ideal ideas, Nurcholish Madjid proposes Pondok Modern Gontor as an ideal pesantren in this modern era. ملخص: تتمثل إحدى أفكار نور خالص مجيد في إندونيسيا في الكشف عن أهمية تحديث التعليم في المعاهد الإسلامية. لذلك ، سيتم الكشف عن بعض المشاكل في هذا البحث. أولاً ، كيف الهدف المثالي للمعاهد الإسلامية وفقًا لنور خالص مجيد؟ ثانيًا، كيف رأي نور خالص مجيد عن المنهج المثالي للمعاهد الإسلامية في عصر التحديث؟ للإجابة على هذه المشكلات، استخدم الباحثان طريقة البحث النوعي بمنهج تحليل المحتوى من خلال البحوث المكتبية. بناءً على نموذج القراءة، يتم إنتاج العديد من أراء نور خالص مجيد. أولاً، يجب أن تكون صياغة أهداف المعاهد الإسلامية مواكبة للعصر. ثانياً، يجب أن تكون المعاهد الإسلامية حلولا لاحتياجات الطلاب في هذا العصر الحديث. في هذه الأفكار المثالية، اقترح نور خالص مجيد يكون معهد دار السلام كونتور نموذجا مثاليا للمعاهد بإندونيسيا في هذا العصر الحديث.